BANKING CONCENTRATION AND FINANCIAL CRISES. (November 2020) - Barrell, Ray; Karim, Dilruba
Abstract : Policymakers need to know if the structure of competition and the degree of banking market concentration change the incidence of financial crises. Previous studies have not always come to clear conclusions. We use a new dataset of 19 countries where we include capital adequacy and house price growth as factors affecting crisis incidence, and we find a positive role for bank concentration in reducing incidence. In addition, we look at New Industrial Economics indicators of market structure and find that increased market power also reduces crisis incidence. We conclude that attempts to increase competition in banking, although welcome for welfare reasons, should be accompanied by increases in capital standards.